2013
DOI: 10.1037/a0030659
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in pedophiles: Automatic and controlled attentional processes while viewing prepubescent stimuli.

Abstract: Recent theories in sexuality highlight the importance of automatic and controlled attentional processes in viewing sexually relevant stimuli. The model of Spiering and Everaerd (2007) assumes that sexually relevant features of a stimulus are preattentively selected and automatically induce focal attention to these sexually relevant aspects. Whether this assumption proves true for pedophiles is unknown. It is aim of this study to test this assumption empirically for people suffering from pedophilic interests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 54 publications
4
39
0
1
Order By: Relevance
“…In contrast, concerning automatic attentional processes, the eye-tracking method demonstrated that the ADT did not affect the initial orienting reaction on sexually deviant stimuli: Before and after treatment the patient showed lower fixation latency for images of girls than for images of women. Our previous studies demonstrated fixation latency as a parameter for automatic attentional processes representing the individual sexual preference [36,37]. We conclude that the antiandrogen medication had no impact on the pedophilic preference of the patient.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, concerning automatic attentional processes, the eye-tracking method demonstrated that the ADT did not affect the initial orienting reaction on sexually deviant stimuli: Before and after treatment the patient showed lower fixation latency for images of girls than for images of women. Our previous studies demonstrated fixation latency as a parameter for automatic attentional processes representing the individual sexual preference [36,37]. We conclude that the antiandrogen medication had no impact on the pedophilic preference of the patient.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the assumption of Spiering et al [35] that sexually relevant features of a stimulus are preattentively selected and automatically trigger focal attention to these sexual aspects, the authors illustrated that the eye tracking method provides the possibility to measure the assumed bias in initial orienting and the maintenance of attention to pedophilic stimuli in pedophiles [36,37]. …”
Section: Introductionmentioning
confidence: 99%
“…Pedophiles demonstrated significantly shorter fixation latencies and significantly longer relative fixation times for child stimuli than either of the control groups. Pedophilic and nonpedophilic individuals could be classified with high sensitivity (86.4%) and specificity (90%) (117,118). Concerning susceptibility to manipulations, a first study demonstrated that healthy hetero-and homosexual subjects (N = 32) could be discriminated with moderate sensitivity (77%) and specificity (86%), even though they had to mask their sexual orientation, while viewing sexual stimuli (119).…”
Section: Eye Trackingmentioning
confidence: 99%
“…Therefore, using the CPAP could offer new insights, as previous oculomotoric approaches refer to later, supposedly more controllable processes (e.g., time to first fixation > 800 ms, Fromberger et al, 2013; time to first fixation > 700 ms, Dawson & Chivers, 2016).…”
Section: Discussionmentioning
confidence: 99%